On the Analysis of Large Numbers of p‐values. (24th April 2019) - Cox, David R.; Kartsonaki, Christiana
Summary: Methods for the analysis of large numbers of p ‐values, observed levels of significance, are reviewed with some emphasis placed on the Rényi decomposition hinging on the relation with independent exponentially distributed random variables. Some extensions are described. An empirical example is used in illustration, and simulation results examining potential complications are outlined.